GAMBARAN POST TRAUMATIC STRESS DISORDER, GANGGUAN TIDUR, KECEMASAN, DAN GEJALA DEPRESI KORBAN GEMPA BUMI DI CIANJUR - Rohmah, Ulfa Nur; Harahap, Sarah Geltri; Yari, Yarwin; La Ramba, Hardin; Ludovikus, Ludovikus; Mailintina, Yurita; Pipin, Apriliana; Sabarina, Ribka (Faculty of Nursing and Midwifery, Binawan University, 2023)
Tectonic earthquakes in Indonesia often occur, there are even earthquakes that result in damage and loss of property and lives. This is because the Indonesian region is one of the regions with a quite complex tectonic order and has a fairly active frequency in the world. This article aims to evaluate the description of PTSD, sleep disorders, anxiety, and symptoms of depression in earthquake victims in Cianjur. This research is a quantitative descriptive research with a population of residents aged (17–60 years) who have experienced the aftermath of the natural disaster in Cianjur, West Java at the end of November 2022. The sampling technique for this study used simple random sampling. The total sample was 54 respondents, with the criteria of the respondent being able to read and write. The results showed that there were not many respondents who experienced PTSD after the natural disaster, almost more than half of the respondents experienced sleep disorders, many respondents also experienced anxiety and depression after the earthquake natural disaster in Cianjur, West Java. Adequate strategies and practices regarding the mental health of earthquake victims are needed